HUBUNGAN CITRA MEREK DAN TINGKAT KEPERCAYAAN MEREK VASELINE DENGAN TINGKAT LOYALITAS KONSUMEN HAND AND BODY LOTION VASELINE - Alexandra Parahita Bening Kesumaputri; Tandiyo Pradekso; Yanuar Luqman (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Nowadays, people giving more attention to use body care. Seeing this phenomenon, many Hand and Body Lotion products spread over the market, including Vaseline. Brand Vaseline first introduce in 1877, while Hand and Body Lotion Vaseline have existed in Indonesia since 1969 until today. It shows that Vaseline brand already won the public trust. Vaseline also do many efforts to increase their positive image, such as using the tagline 'Vaseline, the power of repairing' and carrying a positive beauty vision. Even though Vaseline do a lot of strategy, their hand and body lotion customer loyalty rate has seen decrease since 2016. This study aims to determine the relationship between brand image and brand trust of Vaseline with consumer loyalty of Vaseline Hand and Body Lotion in DKI Jakarta. The theories used in this research are cognitive learning theory, reasoned action theory, and attribution theory. The results of the multiple linear correlation test showed that the brand image and brand trust of Vaseline simultaneously had a relationship with consumer loyalty of Vaseline Hand and Body Lotion users with a significance value of 0.045. In addition, the correlation test of the Vaseline brand image with consumer loyalty of Vaseline Hand and Body Lotion shows a significance value of 0.050 and the relationship between Vaseline brand trust and consumer loyalty of Vaseline Hand and Body Lotion shows a significance value of 0.014, which means there is a relationship between these variables.